MEDIA COMMUNICATIONS IN THE INFORMATION STRATEGY OF UKRAINE'S INTEGRATION INTO THE EU - Leonid Novokhatko (Інтегровані комунікації)
The article is devoted to the importance and role of media communications in Ukraine's European integration processes. The topic of Ukraine's integration into the European Union is vital not only for the political, economic, security, and humanitarian aspects of the state's life but also for the national media space. The importance of the information and communication component for achieving strategic goals is confirmed. The functions of media communications in the context of Ukraine's European integration are defined. The information and analytical activities of Ukrainian media in the national media space on the country's path to the EU are analyzed. Attention is also focused on the problematic issues of covering the topic of European integration. A content analysis of the monitoring of world media for the relevance of the problem under study was conducted using the Media Cloud platform.